Variable selection for proportional hazards models with high-dimensional covariates subject to measurement error - CHEN, Baojiang; YUAN, Ao; YI, Grace Y. (Canadian journal of statistics, 2021)
Methods of analyzing survival data with high-dimensional covariates are often challenged by the presence of measurement error in covariates, a common issue arising from various applications. Conducting naive analysis with measurement-error effects ignored usually gives biased results. However, relatively little research has been focused on this topic. In this article, we consider this important problem and discuss variable selection for proportional hazards models with high-dimensional covariates subject to measurement error. We propose a penalized “corrected” likelihood-based method to simultaneously address the measurement-error effects and perform variable selection. We establish theoretical results including the consistency, the oracle property and the asymptotic distribution of the proposed estimator. Simulation studies are conducted to assess the finite sample performance of the proposed method. To illustrate the use of our method, we apply the proposed method to analyze a dataset arising from the breast cancer study. Les méthodes d’analyse pour les données en haute dimension sont souvent mises à l’épreuve par la présence d’erreurs de mesure dans les variables, un problème commun qui survient dans diverses applications. Le fait de procéder à une analyse naïve qui ignore les erreurs de mesure conduit généralement à des résultats biaisés, mais peu de recherches portent sur ce problème. Les auteurs considèrent cet enjeu et abordent la sélection de variables pour les modèles à risques proportionnels avec des covariables en haute dimension sujettes aux erreurs de mesure. Ils proposent une méthode corrigée basée sur la vraisemblance pénalisée afin de gérer simultanément l’effet des erreurs de mesure et la sélection de variables. Ils établissent des résultats théoriques de l’estimateur, notamment sa convergence, sa propriété d’oracle et sa distribution asymptotique. Les auteurs présentent des études de simulation pour évaluer la performance de leur méthode sur des échantillons finis. Ils l’illustrent également en analysant des données réelles provenant d’une étude sur le cancer du sein.